(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As cities are growing, the government-mandated the builders to construct recycling plants. These production plant uses organic wastes as raw material for the recycling process. Main objective of the optimization is to calibrate the actual state of a process about a certain property through regulated variation of influencing factors in such a way as to achieve definite goals. In this study, we concentrated on the production of biogas, quality of feed, improper maintenance of generators, temperature controls are the factors that affect the production of biogas, keeping all these in mind we took three different plants for the study, here we developed a goal programming model which minimize the underutilization of feeding to the plant, maximize the running hours of the generator, maximize the power supply to the grid, minimize the underutilization of utilization of produced electricity, and minimize the production of manure by calculating quantity of biogas produced.